FRI0358 Contribution of the Adhesion Receptor DNAX Accessory Molecule-1 (DNAM-1) in the Development of Experimental Arthritis. (10th June 2014) - Elhai, M.; Chiocchia, G.; Lager, F.; Allanore, Y.; Avouac, J.
Abstract : Background: Rheumatoid arthritis (RA) is a frequent disease leading to joint destruction, deformity, and loss of function. Its pathogenesis results from the combination of genetic susceptibility genes and environmental factors. Recently, a non-synonymous single nucleotide polymorphism Gly307Ser (rs763361) in the CD226 gene, encoding the DNAX accessory molecule 1 (DNAM-1), has been associated with different autoimmune diseases including RA. Moreover, the functional role of DNAM-1 has been demonstrated in vivo in animal models of multiple sclerosis and dermal fibrosis. Objectives: We aimed to determine the impact of DNAM-1 in the development of arthritis in vivo in a widely used mouse model: the collagen-induced arthritis (CIA) model, using two complementary approaches: a targeted molecular approach with neutralizing anti-DNAM-1 monoclonal antibody (mAb) and a gene inactivation strategy using mice lacking DNAM-1 (dnam1-/-). Methods: CIA was induced in DBA/1 mice, treated in parallel with a DNAM-1 neutralizing monoclonal antibody, a control IgG and PBS, respectively. CIA was also induced in dnam1-/-mice and control dnam-1+/+ mice on a C57/BL6 background. Mice were monitored for clinical and ultrasound signs of arthritis. Histological analysis was performed to evaluate inflammatory infiltrates and erosions. Results: Clinical evidence of arthritis was observed in 5/7 (71%) mice treated with anti-DNAM-1 mAb, 6/7 (86%) mice treated with control IgG, and 7/7 (100%) mice injected with PBS (p=0.1). There was also a non-significant trend for lower clinical, ultrasound and histological scores in mice receiving anti-DNAM-1 mAb. Although not significant, our results suggested a trend toward a less arthritic phenotype in mice treated with anti-DNAM-1 mAb. However, molecular targeted strategy is characterized by an incomplete blockade of the pathway targeted, unlike the gene inactivation strategy. Therefore to better assess the effect of DNAM-1 inhibition for the prevention of CIA, we performed a gene inactivation strategy using dnam1-/- mice. In all, 7/7 (100%) dnam1+/+ versus 4/5 (80%) dnam1-/- mice developed clinical arthritis (p=0.2). Clinical, ultrasound and histological scores were similar in dnam1+/+ and dnam1-/- mice. Collagen antibodies levels were similar in all mice, confirming immunization with collagen. Conclusions: These complementary approaches failed to demonstrate the implication of DNAM-1 in the development of CIA. These findings do not confirm the results of the genetic studies on the role of DNAM-1 in RA. Further studies are now needed to confirm or not the contribution of DNAM-1 in other autoimmune conditions. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4931